Histopathological Study of Urinary Bladder Cancer in a Group of Iraqi Patients from 2019 to 2024 - Salman, Zhraa D.; Mohamad , Ban J. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Urinary bladder cancer (UBC) is the most common urinary tract malignancy, ranking tenth worldwide. In Iraq, UBC is ranked as the seventh most prevalent cancer among the top 10 cancers. Numerous established risk factors for bladder cancer including genetic and hereditary factors, smoking and nicotine behaviors, occupational exposure to certain chemicals and pigments, and environmental pollution from drinking water contaminated with arsenic may also be problems, as well as disorders including chronic cystitis, and infectious diseases like schistosomiasis. Urine cytology and cystoscopy are the gold standard for detecting UBC.Objectives: To analyze and characterize urinary bladder cancer (UBC) diagnosed in a group of Iraqi patients.Cases and methods: A total of 70 paraffin-embedded tissue blocks of bladder cancer were obtained from the archive of the Histopathology Unit of the Martyr Ghazi Al-Hariri/ Medical City, Al-Yarmouk Teaching Hospital, and several private laboratories in Baghdad, Iraq for cases diagnosed between 2019 and 2024. Clinical data in addition to the age and sex of the patients were collected from the patients' clinical records. Histological examination was conducted to determine the tumor characteristics including type, tumor age, sex, size, stage, and grade.Results: The results revealed that 82.9% of UBC cases were males, and 62.9% were between the ages of 60 and 79 years. The most common tumor size was 2-5 cm, with stage T1 accounting for 80% of the total. A high tumor grade was observed in 60% of UBC cases. The most prevalent histological type observed was papillary urothelial carcinoma (77.1%).Conclusion: UBC was found to be mainly a disease of males and older age. Papillary urothelial carcinoma was the most frequently seen, mostly at stage T1 and high grade, more likely to be of a small or moderate size.